In Praise of Mistakes - Lockwood, Mike (Frontiers in Astronomy and Space Sciences, 2022)
Mistakes are a key driver of scientific progress. We should do all we can to eliminate them, partly to keep the literature record clean, but also because expunging what is wrong often leads us to understand what is right.